2010
DOI: 10.1063/1.3386386
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment to pentaerythritol tetranitrate: Significant fragmentation near 0 eV

Abstract: Gas phase dissociative electron attachment (DEA) measurements to pentaerythritol tetranitrate (PETN) are performed in a crossed electron-molecular beam experiment at high-energy resolution and high sensitivity. DEA is operative at very low energies close to approximately 0 eV showing unique features corresponding to a variety of fragment anions being formed. There is no evidence of the parent anion formation. The fragmentation yields are also observed for higher electron energies and are operative via several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…22) lending evidence to their more explosive character when compared to other explosives such as TNT 20 and the other nitrocompounds. [16][17][18][19]23,24,26 In Figure 3 we show the fully optimized geometry obtained at MP2/6-311++G(2d,p)…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…22) lending evidence to their more explosive character when compared to other explosives such as TNT 20 and the other nitrocompounds. [16][17][18][19]23,24,26 In Figure 3 we show the fully optimized geometry obtained at MP2/6-311++G(2d,p)…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26] They have been performed in crossed electron-molecular beam experiments with high-energy resolution (~70 meV) 22 or high sensitivity (utilizing ~10 A of electron current). 27 These experiments have included free electron interactions with bare molecules in the gas-phase [16][17][18][19][20][21][22][23][24][25][26] and embedded in He droplets. 28 In the former, and generally speaking, we have observed that capture of an excess electron with virtually no kinetic energy leads to formation of a variety of dissociative electron attachment (DEA) fragments reflecting therefore the explosive nature of the compounds, whereas in the latter the ultra-cold environment efficiently quenches all the gas-phase dissociation channels.…”
Section: Introductionmentioning
confidence: 99%
“…The DEA to pentaerythritol tetranitrate (PETN) was investigated in energy‐dependent (electron monochromator) cross‐beam experiments in vacuum (MS) . The most important ions detected are NO 3 – (80.5%), NO 2 – (11.1%), O – /OH – (3.5%) and N 2 O 4 – (1.4%) in addition to ions containing carbon, such as C 3 H 3 O – (1.6%).…”
Section: Resultsmentioning
confidence: 99%
“…Electron attachment to trinitrotoluene (TNT) in nitrogen as a drift gas at atmospheric pressure leads to the formation of TNT – . The primary processes governing electron attachment in vacuum were studied using a hemispherical electron monochromator for the production of electrons with a kinetic energy near 0 eV in a mass spectrometer . The product ion spectra obtained in vacuum and at atmospheric pressure display considerable differences .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation